2014
DOI: 10.1016/j.jams.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cord Dorsum Potentials Evoked by Electroacupuncture Applied to the Hind Limbs of Rats

Abstract: The longitudinal distribution of the cord dorsum potentials (CDPs) produced by electroacupuncture (EA) stimulation at acupuncture points (APs) located on the hind limbs of rats was analyzed in this study. Single electrical pulses (0.05 ms, 1 Hz) applied to the bladder (BL) and the gallbladder (GB) APs produced CDPs on several spinal segments and were composed of the following four components: an afferent volley, two negative components (N1 and N2), and one positive component (P wave). The larger evoked CDPs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…53 However, the mechanisms underlying these effects are unclear. GV-EA induces the depolarization of neurons, 54,55 thus leading to the opening of L-type voltage-gated Ca 2+ channels (L-VGCC) and Ca 2+ influx; this process activates calcium/calmodulin-dependent protein kinase (αCaMKII) signaling and the synthesis and secretion of neurotrophic factor (e.g., NT-3). 55 Thus, GV-EA may directly stimulate the afferent nerve fiber endings of the meningeal branch of the SC in adjacent segments and induce the release of CGRP by DRG neurons into the SC.…”
Section: Gv-e Ainduce Sthesynthe S Isand S Ecre Ti Onofneurotrophi Cf...mentioning
confidence: 99%
“…53 However, the mechanisms underlying these effects are unclear. GV-EA induces the depolarization of neurons, 54,55 thus leading to the opening of L-type voltage-gated Ca 2+ channels (L-VGCC) and Ca 2+ influx; this process activates calcium/calmodulin-dependent protein kinase (αCaMKII) signaling and the synthesis and secretion of neurotrophic factor (e.g., NT-3). 55 Thus, GV-EA may directly stimulate the afferent nerve fiber endings of the meningeal branch of the SC in adjacent segments and induce the release of CGRP by DRG neurons into the SC.…”
Section: Gv-e Ainduce Sthesynthe S Isand S Ecre Ti Onofneurotrophi Cf...mentioning
confidence: 99%
“…Importantly, GABA B receptors are not susceptible to the CL− dysregulation that occurs following nerve injury. A recent study demonstrated that electroacupuncture applied within a particular lumbosacral dermatome, synchronously activates DHN that are interconnected in a rostro-caudal manner across multiple spinal segments [ 115 ]. Evidence suggests that presynaptic inhibition is enhanced by increasing the synchronization between pairs of evoked DHN, allowing better modulation of arriving afferent inputs [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…потенциалов поперек спинного мозга в условиях стимуляции целых и перерезанных дорсальных корешков ПДП СМ является интегральным потенциа-лом, который включает в себя ряд суммарных ВПСП нейрональных пулов, возбуждение к которым прихо-дит по афферентным волокнам с определенной ско-рости проведения [8]. Первый негативный (N 1 ) ком-понент (направлен вверх относительно базиса на рис.…”
Section: распределениеunclassified
“…Взаимодействие этих факторов приводит к тому, что в области сег-мента L 5 проявляется наиболее высокоамплитудный N 1 -компонент ПДП, связанный с активацией волокон группы А β . Следует отметить, что клетки данного компонента формируют быстрые восходящие к верх-ним шейным отделам и головному мозгу нервные тракты [6,8] и не участвуют в повторных межсег-ментарных взаимодействиях (ВТ на рис. 3).…”
Section: обсуждение результатов изучения попе-речного распределение вunclassified